Gender Sensitive Journalism; The Role of Magdalene Online Media in Campaigning for Gender Issues - Puji Laksono; Laila Aisya Zakiyah (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2023)
As a general rule, this exploration is inspired by the peculiarity of digitization and the peculiarity digitalization and the presence of a virtual world that gives another variety to social reality. Then, the researcher looked at online journalism activity, whose movement is massive in the cyber world. Specifically, this reseach is driven by a social construction and patriarchal system that creates gender inequality. For this situation, the act of news-casting in the computerized space can assume a part in battling the tide and advancing orientation uniformity, as rehearsed by Magdalene. Magdalene is a women's activist elective media established in 2013 by Devi Asmarani and Hera Diani. Magdalene applies gender-sensitive journalism practices and campaigns for various issues; orientation, compassion, ecological, and strategy issues. The researcher uses a qualitative type and case study method in this study. Get information sources from observations, interviews, documentation, and literature studies. Magdalene has numerous web-based entertainment, but; this research only explored the site magdalene.co and the Instagram account @magdaleneid. The outcomes showed; Magdalene is a press media since it does its press capability well. In journalism, Magdalene stays directed by the overarching set of rules, yet what matters is; Magdalene takes a feminist point of view and represents minorities. Magdalene has objectives; disperse orientation and well-disposed understanding. Through computerized networks, Magdalene conducts crusades, introducing an assortment of printed and visual substances, which is then bundled daintily (influentially) with the goal that the crowd effectively processes it.